Pengaruh Pemberian Permainan Kung Fu Matematika terhadap Kemampuan Berhitung Anak Usia Dini - Rosa Imani Khan; Veny Iswantiningtyas; Saiful Efendi (Program Studi PGRA, 2018)
This study aims to determine whether there is influence of giving Math Kung Fu game to the ability of early childhood counting. Development activities of children's numeracy skills can be done through a game that would be more effective because the world of children is a world of play. Subjects in this study, as an experimental group is 20 children in Group A TK Dharma Wanita Punjul 3 District Plosoklaten Kediri. While as a control group is 19 children in Group A TK Dharma Wanita Gogorante Kediri Regency. Both groups are considered to have common characteristics common to this study. The sample selection is done by convenience sampling technique, the researcher has no other consideration except based on convenience only. This type of research is quasi-experimental research, using a non-randomized pretest-posttest control group design. The design of this study was conducted by providing pretest before treatment was administered and posttest after treatment, as well as a control group and experimental group. In this design, the sample is set with no random. Instrument of data collection in this research is performance assessment sheet with scale of appraisal, using observation and performance technique. Data analysis was done by t-two sample test with SPSS for windows version 16. The Paired-Samples T Test analysis shows the test results of 3.383 and the mean difference of 1.263. Sig value obtained is 0.003, smaller than alpha specified that is 0.05. This shows that there is a significant difference between the mean values of children in the experimental group and the control group. The Paired Samples Statistics analysis shows the mean value in the experimental group of 13.05 and in the control group of 10.79. This shows that the mean posttest score of children in the experimental group is better than the control group. This means that there is a positive and significant influence on the giving of the Math Kung Fu Game to the ability of early childhood counting. The ability to count children develops after playing Math Kung Fu.